RNA-binding protein IGF2BP2 suppresses metastasis of clear cell renal cell carcinoma by enhancing CKB mRNA stability and expression - Junwu Ren; Bo Huang; Wei Li; Yongquan Wang; Xiaojuan Pan; Qiang Ma; Yuying Liu; Xiaolin Wang; Ce Liang; Yuying Zhang; Shimin Wang; Feifei Yang; et al. (Translational Oncology, 2024)
Clear cell renal cell carcinoma (ccRCC) is the most prevalent kidney cancer, with a highly aggressive phenotype and poor prognosis. RNA binding proteins (RBPs) play crucial roles in post-transcriptional gene regulation and have been implicated in tumorigenesis. RBPs have the potential to become a new therapeutic target for ccRCC. In this study, we screened and validated that insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) as an RBP, was down-regulated in ccRCC tissues and cell lines. Functionally, we verified that IGF2BP2 significantly suppressed the migration and invasion ability of ccRCC in vitro and in vivo. Mechanistically, RIP-seq and actinomycin D experiments results showed that IGF2BP2 enhanced the expression of Creatine Kinase B (CKB) by binding to CKB mRNA and enhancing its mRNA stability. Thus, IGF2BP2 inhibited ccRCC metastasis through enhancing the expression of CKB. Taken together, these finding suggests that IGF2BP2 is a novel metastasis suppressor of ccRCC and may serve as a potential therapeutic target.